The Growth of Arctic Marine Phytoplankton in Frobisher Bay - Hsiao, Stephen I.C. (ARCTIC, 1985)
During the summers of 1977 and 1978, populations of phytoplankton collected in Frobisher Bay at depths of 0, 5, 10, 15, 20 and 25 m were enclosed in dialysis bags and incubated in situ at the depths from which they were collected. The greatest growth rate of the populations occurred at 10 m in July-August 1977 and at 5 m in late August-early September 1978. Exponential growth rates and generation times of dominant species of phytoplankton are tabulated. Growth rates ranged from 0.06 to 1.12 division/day and generation times varied from 21.4 to 404.7 hr/division. Light appears to be the major limiting factor for phytoplankton growth in this area; nutrients, temperature and salinity were not limiting in this experiment.Key words: growth rates, generation times, arctic marine phytoplankton, limiting factors Mots clés: les taux de croissance, les temps de génération, phytoplancton marine de l'arctique, des facteurs limitants